Laughter and Humour in the Life of the Prophet Muhammad (PBUH) and His Companions: A Critical Exploration - Ahmed, Shoayb (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
Laughter and humour in the life of the Prophet Muhammad (PBUH) and his Companions have often been underexplored within the context of Islamic scholarship, yet they offer valuable insights into the human dimensions of Islamic teachings. This paper employs a qualitative, historical research methodology to examine the role of humour in the life of the Prophet Muhammad and his closest associates, as documented in early Islamic sources, particularly Hadith literature. Through a critical textual analysis of authentic narrations, the study employs thematic and hermeneutic approaches to explore how humour functioned as a tool for building community, fostering compassion, and diffusing tension. The paper also utilises a comparative analysis of various Hadiths to illustrate the Prophet's use of humour, revealing how his light-hearted interactions were framed not as frivolous but as expressions of wisdom, kindness, and accessibility. Additionally, a sociocultural analysis is applied to explore how the Prophet's Companions, including utilising humour in their daily lives, reflect the ethical and social dimensions of laughter in early Islamic society. The study further contextualises humour within the broader social and moral frameworks of early Islam, assessing how it reinforced community cohesion, challenged arrogance, and emphasised the transient nature of worldly life. Ultimately, this study underscores that laughter and humour in the life of the Prophet and his Companions were integral to cultivating humility, empathy, and a deeper understanding of the divine. By examining the intersection of humour with faith through a multidimensional approach, this paper contributes to a richer understanding of Islamic ethics and spirituality, demonstrating that laughter, in its proper context, can be a meaningful aspect of the believer’s relationship with God and society.